2015
DOI: 10.1002/jso.24075
|View full text |Cite
|
Sign up to set email alerts
|

Previous radiation for prostate neoplasm alters surgical and oncologic outcomes after rectal cancer surgery

Abstract: This is the first report of altered survival rates after proctectomy in patients who had previously received radiation for PC. Postoperative morbidity and definitive defunctioning stoma rates were significantly increased in these patients with poor prognoses. Therapeutic strategies should thus be individualized. Large, multicenter cohort studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…In our historical study [1], we showed 50% with anastomotic leakage and 50% with Dindo III-V complications. Guandalino et al [2] showed 62.5% with anastomotic leakage and 25% of with definitive stoma in eight patients with previous radiotherapy for prostate cancer. Lakkis et al [3], in a French multicentre retrospective study comparing patients treated for rectal cancer with and without previous curative treatment for prostate cancer, found major surgical morbidity (28% vs 17.2%), anastomotic leakage (25% vs 13.7%) and permanent stoma (41% vs 12.4%) more frequently in patients with a history of prostate cancer treated with high-dose radiotherapy, prostatectomy or brachytherapy.…”
Section: Discussionmentioning
confidence: 96%
“…In our historical study [1], we showed 50% with anastomotic leakage and 50% with Dindo III-V complications. Guandalino et al [2] showed 62.5% with anastomotic leakage and 25% of with definitive stoma in eight patients with previous radiotherapy for prostate cancer. Lakkis et al [3], in a French multicentre retrospective study comparing patients treated for rectal cancer with and without previous curative treatment for prostate cancer, found major surgical morbidity (28% vs 17.2%), anastomotic leakage (25% vs 13.7%) and permanent stoma (41% vs 12.4%) more frequently in patients with a history of prostate cancer treated with high-dose radiotherapy, prostatectomy or brachytherapy.…”
Section: Discussionmentioning
confidence: 96%
“…Small retrospective studies have suggested increased surgical morbidity in rectal cancer surgery following high‐dose RT. No association between previous prostate cancer treatment including prostatectomy and rectal cancer surgery outcomes has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…After previous pelvic radiotherapy for PC, the management of colorectal tumours that would usually necessitate AR remains challenging for surgeons. Previous pelvic radiation increases the risk of intra-operative ureteric injury and post-operative anastomotic leak in AR [ 2 , 3 ]. Guandlaino et al showed that previous radiation for PC was associated with anastomotic leak rate of 62.5% compared to 12.5% in those who had not received such treatment [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate and rectal cancers are the most common pelvic malignancies affecting the male population [ 1 , 2 ]. Given that 10% of men will develop prostate cancer (PC) and that external beam radiotherapy (EBRT) is commonly used for treatment, many patients diagnosed with rectal cancer will have already received radical radiotherapy, with significant implications for management [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation